The effectiveness of making comics as innovative learning media: A study on prospective elementary school teachers - Meriza Faradilla; Anggi Susilawati; Khairul Rizal (Pelita International Publishing, 2024)
Comics are one of the teaching materials developed as a tool in the learning process according to a particular topic or material. Therefore, as prospective teachers, students must be able to design and develop teaching materials in the form of comics and apply them in learning in elementary school according to the expected learning objectives. This study aims to see the effectiveness of students in making learning comics as innovative learning media. The type of research used is descriptive qualitative, with data collection through observation. The research sample was 4th-semester Elementary School Teacher Education (PGSD) students. The results of the content validity test, language, presentation, and graphics were in the valid category. Presentation and discussion skills, as well as student activities based on the results of observations, were stated to be good.